Utilization Of Tofu Dregs Flour Fermented With Aspergillus niger In Feed On The Growth Of Nilem Fish (Osteochilus hasselti) - Nova Sintya Sary; Indra Suharman; Adelina Adelina (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
This research was conducted for 56 days which aims to determine the effect of the use of fermented tofu dregs flour A. niger in feed on feed efficiency and growth of nilem fish fry. This study used a completely randomized design (CRD) with 5 levels of treatment with 3 replications. The test feed used was artificial feed with a protein content of 30% and containing fermented tofu dregs flour (TATF) of 0, 25, 50, 75 and 100%. The test fish used were nilem fish with an average weight of 1.73 ± 0.05 g. The fish were kept in cages measuring 1x1x1 m3 as many as 15 units with a stocking density of 25 fish of water volume. The container used for observing the digestibility parameters was an aquarium measuring 60 x 40 x 40 cm with a total of 20 fish per aquarium. The feed used for observing the digestibility and protein digestibility parameters was added with 0.5% Cr2O3 of the total feed. The test feed was given 3 times a day as much as 10% of the weight of the biomass, namely at 07.00, 12.00 and 17.00 WIB. The results showed that the use of fermented tofu dregs flour had a significant effect (P<0.05) on growth and feed efficiency. Based on the results obtained, it can be concluded that soybean flour can be substituted 100% by fermented tofu pulp flour for nilem fish feed with tilapia feed digestibility 53.83%, protein digestibility 79.78%, feed efficiency 33.90%, protein retention 24.93 %, the specific growth rate is 3.48% and the survival rate is 100%.